1984
DOI: 10.1073/pnas.81.6.1679
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an angiotensin II-binding protein from liver.

Abstract: A protein that specifically binds angiotensin II has been isolated in nearly homogeneous form by two independent approaches after solubilization from rabbit liver particles by treatment with digitonin. The protein purified by either of these methods resembles in size the single radioactive macromolecular component made by using disuccinimidyl suberate to crosslink radioiodinated angiotensin II with its receptor in the solubilized extract. In the first technique, angiotensin II as an affinity ligand specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…On the basis of this evidence, we have used the MGYsrc peptide as a probe in membrane cross-linking studies to identify potential pp6Qsrc binding proteins. This experimental rationale is based on the ability to use radiolabelled small ligands as probes to identify membrane-bound receptors and has been successfully exploited by other investigators to identify the receptors for, e.g., gamma interferon, erythropoietin, angiotensin II, and parathyroid hormone (21,29,31,39).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this evidence, we have used the MGYsrc peptide as a probe in membrane cross-linking studies to identify potential pp6Qsrc binding proteins. This experimental rationale is based on the ability to use radiolabelled small ligands as probes to identify membrane-bound receptors and has been successfully exploited by other investigators to identify the receptors for, e.g., gamma interferon, erythropoietin, angiotensin II, and parathyroid hormone (21,29,31,39).…”
Section: Discussionmentioning
confidence: 99%
“…An essential step towards comprehension of the mechanism of action of All is the elucidation of its receptor structure. The major drawback to the physical characterization and purification of the All receptor has been the difficulty in solubilizing the protein in a sufficiently stable and active form (Brecher et al, 1974;Devynck et al, 1974;Forget & Heisler, 1979;Capponi & Catt, 1980;Sen et al, 1984). Some groups of workers have been able to recover binding activity after solubilization, but their methods have not led to further purification or characterization of the receptor (Chang & Lotti, 1981;Capponi et al, 1983;Sen et al, 1983;Akiyama et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ang II has been shown to bind to a high-affinity cytoplasmic Ang II binding protein in non-renal tissues, although the consequences of this interaction remain to be determined. 22,78,109,110 To determine whether intracellular or internalised Ang II plays any physiological role in proximal tubule cells, microinjection of Ang II directly into the cells may be one of the best approaches available, because it can differentiate the intracellular effects mediated by the microinjected Ang II from those mediated by extracellular Ang II via membrane receptors. Using this novel approach, we recently demonstrated that microinjection of Ang II into proximal tubule cells induced intracellular [Ca 2+ ] i responses and the responses were blocked by co-microinjection with the AT 1 -receptor agonist losartan or by pre-treatment of the cells with thapsigargin to deplete intracellular calcium stores or with U-73122 to inhibit phospholipase C. …”
Section: Internalised Ang II Induces Intracellular Calcium Mobilisatimentioning
confidence: 99%